Evolutionary Adaptations of Plant AGC Kinases: From Light Signaling to Cell Polarity Regulation - Rademacher, Eike H.; Offringa, Remko (Frontiers in Plant Science, 2012)
Signaling and trafficking over membranes involves a plethora of transmembrane proteins that control the flow of compounds or relay specific signaling events. Next to external cues internal stimuli can modify the activity or abundance of these proteins at the plasma membrane. One such regulatory mechanism is protein phosphorylation by membrane-associated kinases and phosphatases. The AGC kinase family is one of seven kinase families that are conserved in all eukaryotic genomes. In plants evolutionary adaptations introduced specific structural changes within the plant AGC kinases that most likely allow for sensing of external stimuli (i.e. light) through controlled modification of kinase activity. Starting from the well-defined structural basis common to all AGC kinases we review the current knowledge on the structure-function relationship in plant AGC kinases. Nine of the 39 Arabidopsis AGC kinases have now been shown to be involved in the regulation of auxin transport. In particular, AGC kinase-mediated phosphorylation of the auxin transporters ABCB1 and ABCB19 has been shown to regulate their activity, while auxin transporters of the PIN family are located to different positions at the plasma membrane depending on their phosphorylation status, which is a result of counteracting AGC kinase and PP2A phosphatase activities. We therefore focus on regulation of AGC kinase activity in this context. Identified structural adaptations of the involved AGC kinases may provide new insight into AGC kinase functionality and demonstrate their position as central hubs in the cellular network controlling plant development and growth.